The Use of Action Research in the Management of Environmental Problems - DOI: 10.3395/reciis.v1i1.37en - Michel Thiollent; Generosa de Oliveira Silva (Instituto de Comunicação e Informação Científica e Tecnológica em Saúde (Icict) da Fundação Oswaldo Cruz (Fiocruz), 2007)
The aim of the article is to present and discuss the possibilities for using participatory methodologies and action research in studies with a socioenvironmental focus, particularly in the rural context. Special emphasis is given to problems which occur as a result of interactions between researchers and communities and ways of building a shared vision are suggested. Finally, the article presents some results from a participatory project involving communities in a microbasin in the north-west region of Rio de Janeiro state, relating in particular to the health problems resulting from the use of pesticides. The procedures used to deal with the organization of the communities are also highlighted.